Communication Strategy of the Indonesian Kabaddi Federation (FOKSI) Central Java for Image and Popularity - Bungaran Saragih; Limpad Nurrachmad (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Research on sport communication has concentrated on established mainstream sports, leaving emerging sport organizations underexplored. This study analyzes how the All-Indonesia Kabaddi Sports Federation (FOKSI) of Central Java builds kabaddi image and popularity, an emerging sport facing low recognition and limited media exposure. A constructivist interpretive qualitative case study was conducted; data were gathered through semi-structured interviews and docu-mentation from eight informants and analyzed thematically following Miles and Huberman. The findings reveal an "achievement based communication strategy" in which credibility is sequenced before visibility: athletic achievement is con-verted into symbolic legitimacy amplified through athlete-led storytelling, decen-tralized social media generating electronic word of mouth, and a hybrid of mass media partnership and event-based engagement. The study extends strategic sport communication by positioning symbolic legitimacy and organizational rep-utation as the mediating mechanism linking communication strategy to populari-ty in resource constrained, emerging-sport contexts, while identifying funding constraints, vacant regional boards, and low public literacy as structural inhibi-tors. The novelty lies in reframing "achievement first, popularity later" from a practitioner maxim into an analytic model of credibility-led communication, of-fering a transferable framework for developing sports.